Developing social media-based marketing applications to improve rural families' extra incomes - Nurdin I. Muhammad; Alwinda Manao; Ade Risna Sari; Zulqarnain Zulqarnain; Fahima Nasar (Enrichment : Journal of Management, 2023)
Efforts to use various social media applications to support not only friendship but for business marketing not only in cities but even in remote villages today have become something very phenomenal. To answer this problem, how to be digital is developed for community marketing, especially in urban areas, we have obtained several scientific evidence from various sources; it is hoped that we will specialize in publications that were released in the last year, considering the development of digital applications and their involvement in supporting human activities and business governance. As well as private. After getting the amount of data, we then analyzed it under increasing in-depth evaluation, deep integration, and concluding, which, in essence, is getting valid findings to answer the problems of this study. After a series of studies and discussion of the results, the development of social media for various marketing with exciting applications has attracted many business people in cities and families to get additional income. Thus these findings should be helpful for policy-making academics, even for related research studies to be carried out in the future.